Evaluation of Spray Application of a Lactobacillus-based Probiotic on Salmonella enteritidis Colonization in Broiler Chickens - Wolfenden, A.D.; Pixley, C.M.; Higgins, J.P.; Higgins, S.E.; Hargis, B.M.; Tellez, G.; Vicente, J.L.; Torres-Rodriguez, A. (International Journal of Poultry Science, 2007)
Spray application offers low-cost and efficient application of biologic and reduced concerns regarding diverse water quality and medicator/proportioner function. The objective of the present study was to evaluate the spray application of a Lactobacillus-based probiotic on Salmonella enteritidis (SE) colonization in broiler chickens. Day-of-hatch chicks were challenged with Salmonella enteritidis (SE) by oral gavage alone, challenged with SE and treated by coarse spray application of a commercially-availably Lactic-acid bacterial probiotic (FM-B11™), or challenged with SE and treated with B11 continuously in the Drinking Water (DW). Five days post-challenge, cecal tonsils were collected for presence or absence of SE. In Exp. 1, probiotic treatment by either spray or DW application significantly (p